2015
DOI: 10.3390/su7067644
|View full text |Cite
|
Sign up to set email alerts
|

Local Knowledge of Pond Fish-Farming Ecosystem Services: Management Implications of Stakeholders’ Perceptions in Three Different Contexts (Brazil, France and Indonesia)

Abstract: This article addresses ecosystem service perceptions in the case of pond fish-farming systems in Brazil, France and Indonesia. The Millennium Ecosystem Assessment vision suggests a more integrated reflection on environmental policies with greater adaptability to local knowledge and the development of social learning processes, which tend to promote more sustainable changes in behavior and practice than do sanctions. This study considers a part of the identification of ecosystem services. It shows that percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Its high recognition of heritage was an artefact of the highly developed oyster production systems in this region, which certain stakeholders associated with aquaculture. Additional details of stakeholder perceptions can be found in Mathé and Rey‐Valette ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its high recognition of heritage was an artefact of the highly developed oyster production systems in this region, which certain stakeholders associated with aquaculture. Additional details of stakeholder perceptions can be found in Mathé and Rey‐Valette ().…”
Section: Resultsmentioning
confidence: 99%
“…To assess local knowledge and perceptions of ecosystem services, farmers and other stakeholders (Table ) were interviewed using semi‐structured questionnaires (Blayac et al . ; Mathé & Rey‐Valette ).…”
Section: Methodsmentioning
confidence: 99%
“…The CICES has no participatory component; however, it is possible to ask stakeholders to classify or distinguish the typology of the main ES of a specific aquaecosystem. Because the presence of an ES is due to its direct or indirect use, or the recognition of its value (Mathe and Rey-Valette, 2015), surveys can help to specify a suitable local ES typology from those in our typology (Blayac et al, 2014;Rey-Valette et al, 2017). The terminology used by Haines-Young, Potschin (2013) for the CICES may appear too technocratic for participatory approach with a wide diversity of stakeholders.…”
Section: Integration In the Eaamentioning
confidence: 99%
“…Studies are focused on the quantification of several regulation ES as a land-use function (Ditt et al, 2010;Ferraz et al, 2014;Grimaldi et al, 2014;LeClec'h et al, 2016;Mathé and Rey-Valette, 2015). They also involve estimates of soil loss (Tôsto and Pereira, 2015), sediment input into water resources (Chaves, 2010) and the definition of conservation areas (Duarte et al, 2016).…”
Section: Erosion Prevention and Controlmentioning
confidence: 99%
“…Cultural Services are services related to the aesthetic, spiritual, educational and recreational benefits offered by ecosystems. The research found few studies that evaluated people's perception of ES and the relationship they have with their environment (Mathé and Rey-Valette, 2015;Oliveira and Berkes, 2014) and with ecological restoration projects (Brancalion et al, 2014). The studies apply qualitative (Pereira and Campos, 2009;Ribeiro and Ribeiro, 2016;Souza Filho et al, 2014) and quantitative evaluations (Mariano et al, 2015;Rares and Brandimarte, 2014) and economic valuation of ES (Mathé and Rey-Valette, 2015), to point out that aesthetic values and opportunities for recreation and tourism are the most commonly perceived ES.…”
Section: Cultural Servicesmentioning
confidence: 99%